PERBANDINGAN KUAT TEKAN DAN KUAT TARIK LANGSUNG POLIMER MODIFIED MORTAR BERSERAT AGAVE CANTULLA ROXB DENGAN POLIMER MODIFIED MORTAR BERSERAT KACA - Bagas Prabowo; Edy Purwanto; Stefanus Adi Kristiawan (Jurnal Riset Rekayasa Sipil, 2019)
Concrete has some advantages and some deficiencies. The advantage of concrete is the character that concrete can resist from compressive strength and the deficiency of concrete is the character that concrete can’t resist from tensile strength. One of the solution to increase the resistance of concrete from tensile strength is mix the concrete with fiber. The fiber will be used are natural fiber and fabrication fiber. The natural fiber is Agave Cantula Roxb and the fabrication fiber is fiber glass. The fiber that will be mixed to Polymer Modified Mortar is a short fiber that spread randomly. the adding of short fiber has two aspects the first is fiber length and the second is volume fraction. The fiber length is 1,0 cm, 1,5 cm, 2,0 cm, 2,5 cm, 3,0 cm and the volume fraction is 1%, 2%, 3% from the volume of cylinder test object. The test object will be test on 3 days and 28 days for tensile strength test, for compressive strength test the test object will be test on 3 days, 7 days and 28 days. Result of testing is natural fiber have highest tensile strength on fiber length 2,0 cm and the volume fraction is 3% while the fabrication fiber has highest tensile strength on fiber length 2,0 cm and the volume fraction is 2%. The compressive strength and the tensile strength of Polymer Modified Mortar with Agave Cantula Roxb Fiber is not far different from the compressive strength and the tensile strength of Polymer Modified Mortar with Fiber Glass.